An Easy, Convenient Cell and Tissue Extraction Protocol for Nuclear Magnetic Resonance Metabolomics. Issue 4 (23rd January 2014) - Matheus, Nicolas; Hansen, Sylvain; Rozet, Eric; Peixoto, Paul; Maquoi, Erik; Lambert, Vincent; Noël, Agnès; Frédérich, Michel; Mottet, Denis; de Tullio, Pascal; Choi, Young Hae; Verpoorte, Robert
ABSTRACT Introduction As a complement to the classic metabolomics biofluid studies, the visualisation of the metabolites contained in cells or tissues could be a very powerful tool to understand how the local metabolism and biochemical pathways could be affected by external or internal stimuli or pathologies. Therefore, extraction and/or lysis is necessary to obtain samples adapted for use with the current analytical tools (liquid NMR and MS). These extraction or lysis work‐ups are often the most labour‐intensive and rate‐limiting steps in metabolomics, as they require accuracy and repeatability as well as robustness. Many of the procedures described in the literature appear to be very time‐consuming and not easily amenable to automation. Objective To find a fast, simplified procedure that allows release of the metabolites from cells and tissues in a way that is compatible with NMR analysis. Methods We assessed the use of sonication to disrupt cell membranes or tissue structures. Both a vibrating probe and an automated bath sonicator were explored. Results The application of sonication as the disruption procedure led to reproducible NMR spectral data compatible with metabolomics studies. This method requires only a small biological tissue or cell sample, and a rapid, reduced work‐up was applied before analysis. The spectral patterns obtained are comparable with previous, well‐described extraction protocols. Conclusion The rapidity and the simplicity of this approach could represent a suitable alternative to the other protocols. Additionally, this approach could be favourable for high‐ throughput applications in intracellular and intratissular metabolite measurements. Copyright © 2014 John Wiley & Sons, Ltd.